2017
DOI: 10.1103/physrevb.96.214434
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic magnetoresistance across Verwey transition in charge ordered Fe3O4 epitaxial films

Abstract: The anisotropic magnetoresistance (AMR) near the Verwey temperature (T V ) is investigated in charge ordered Fe 3 O 4 epitaxial films. When the temperature continuously decreases below T V , the symmetry of AMR in Fe 3 O 4 (100) film evolves from twofold to fourfold at a magnetic field of 50 kOe, where the magnetic field is parallel to the film surface, whereas AMR in Fe 3 O 4 (111) film maintains twofold symmetry. By analyzing AMR below T V , it is found that the Verwey transition contains two steps, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
0
15
1
Order By: Relevance
“…The anisotropic magnetoresistance (AMR) of highquality epitaxial Fe 3 O 4 films on MgO (100) and Al 2 O 3 (0001) substrates [36] was investigated in charge-ordering state, as shown in Figure 7(a). It was found that the Verwey transition contains two processes, a fast charge-ordering process and a continuous formation of trimeron process.…”
Section: Observation Of Verwey Transition In Various Fe 3 O 4 Nanostrmentioning
confidence: 99%
“…The anisotropic magnetoresistance (AMR) of highquality epitaxial Fe 3 O 4 films on MgO (100) and Al 2 O 3 (0001) substrates [36] was investigated in charge-ordering state, as shown in Figure 7(a). It was found that the Verwey transition contains two processes, a fast charge-ordering process and a continuous formation of trimeron process.…”
Section: Observation Of Verwey Transition In Various Fe 3 O 4 Nanostrmentioning
confidence: 99%
“…The details of fabrication have been published elsewhere. 26 The film thickness of about 200 nm was determined using a Dektak 6M surface profiler and by transition electron microscopy (TEM). Stoichiometry of Fe 3(1-d) O 4 thin films with d less than 3.5 Â 10 À4 was determined by Rutherford backscattering spectroscopy with the precision of 10 À3 -10 À2 at.…”
mentioning
confidence: 99%
“…%. 26 Electronic transport properties of Fe 3 O 4 films were measured using the standard four-probe method using a Quantum Design physical property measurement system. The and Fe 3 O 4 /quartz samples are 117.7, 122.8, and 122.4 K, respectively, which are decided by the maximum slope of logq [see Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there still exist uncertainties as to the precise mechanism responsible for this electrical and structural transition. Further, the consequential influence of magnetic properties on the transition and its electronic characteristic is still unclear, [7][8][9][10] particularly for nanocrystalline Fe 3 O 4 films.…”
Section: Introductionmentioning
confidence: 99%